From Terror to Titans: The Return of Nuclear Great Power Politics and the Decline of the Global War on Terrorism (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the transformation of global security from the counterterrorism-oriented Global War on Terrorism (GWOT) to the re-emergence of nuclear great power politics in a multipolar international system. Employing the theoretical lens of Critical Security Studies (CSS), it critically examines how nuclear threats are discursively framed, securitized, and situated within structural hierarchies that privilege state-centric and militarized approaches over human security concerns. The research adopts a qualitative methodology based primarily on secondary sources, including peer-reviewed academic literature, policy documents, and institutional reports. Through a discursive and normative analytical approach, the study highlights the re-securitization of nuclear weapons, the sidelining of non-state and human security threats, and the perpetuation of inequalities in the global security order. The findings underscore how the renewed emphasis on nuclear deterrence reflects and reinforces systemic power imbalances, while neglecting pressing issues such as climate change, poverty, and public health. The paper concludes by advocating for a re-envisioned global security paradigm that prioritizes inclusive governance and human emancipation.